Relative Growth Relationship between Different Body Parts of the Bivalve Gari virescens and its Shell Length — Allometric Formulas for Shell Length Size Reconstruction - Shigeta, Toshihiro (Venus (Journal of the Malacological Society of Japan), 2024)
Gari virescens (Psammobiidae) is a near-threatened bivalve species that inhabits tidal flats in Japan. Recently, it has been frequently detected in the gut contents of tidal flat fishes. The purpose of this study is to establish regression formulas for reconstructing the shell length (SL) of predated specimens. Therefore, we clarified the relative growth relationship between body parts of the bivalve and its SL using specimens from the western Seto Inland Sea of Japan. The allometric regression formula for estimating SL (mm) from shell height (SH, mm) was SL = 1.53 × SH1.0657 (r = 0.998, n = 66, P < 0.01), and the formula for estimating SL (mm) from foot length (FL, mm) was SL = 1.82 × FL1.0478 (r = 0.969, n = 39, P < 0.01). In addition, we established several other regression formulas for estimating SL. As a case study of applying these formulas, we reconstructed the SL of specimens predated by the fish Acanthopagrus schlegelii. These allometric formulas enable the reconstruction of SL from body parts and shells broken during predation.